Design, Synthesis, and Biological Study of Novel Farnesoid X Receptor Agonist for the Treatment of Cholestatic Liver Disease. Issue 35 (13th September 2022) - Wang, Han; Sun, Yating; Li, Hewei; Yang, Shengli; Yi, Wen
Abstract: Farnesoid X receptor (FXR) plays an important role in regulating bile acid homeostasis, which is considered as an innovative target for cholestasis. In this study, we have hybrid FXR agonists LY2562175 with GW4064, and we introduced the urea linker to avoid the potentially toxic scaffold stilbene in GW4064. These efforts provided FXR partial agonist 1 (EC50 =282 nM, efficacy=70 %), which binds very tightly to the pocket of FXR by forming an ionic bond with Arg331, the residue is vital to the activity of FXR. Indeed, compound 1 exhibited little cytotoxicity in the MTT assay. Moreover, compound 1 revealed a comparative protective effect against ANIT‐induced cholestasis to that of obeticholic acid, the most advanced FXR agonist in this field. Further studies exhibited that partial agonist 1 exerts multiple synergetic mechanisms on bile acid homeostasis in vivo : 1) Decreasing hepatic uptake and increasing efflux of bile acids by regulating the gene expression of Ntcp, Bsep, and Mrp2. 2) Reducing hepatic bile acid synthesis by inhibiting the expressions of Cyp7a1 and Cyp8b1. 3) Increasing hepatic bile acid metabolism by promoting gene expression of Sult2a1. In conclusion, these results suggested that compound 1 is a promising FXR partial agonist suitable for further study. Abstract : To avoid the potentially toxic scaffold stilbene in GW4064, we have hybrid LY2562175 with GW4064 by introducing the urea linker, which provided the promising FXR partial agonist 1 (EC50 =282 nM, efficacy=70 %). Compound 1 exhibited little cytotoxicity and a comparative protective effect against ANIT‐induced cholestasis to that of obeticholic acid, the most advanced FXR agonist in this field.